Towards Equitable Progress Essays from a South Asian Perspective - Gunaratna, K. Locana (South Asia Economic and Policy Studies,, 2018)
This book gathers a collection of essays presented from the perspective of a spatial planner whose working life has been immersed in South Asia. It concerns some of the serious challenges that need to be confronted in the South Asian context, including the externalities and ethical concerns that arise in the process of development. The mid-20th century saw a considerable focus in the West on assisting those countries emerging from European colonial domination. Theories were propounded and international agencies established to facilitate a process called 'development' in these countries. However, even after six decades of extraordinary expenditures and effort, millions among the targeted populations remain illiterate, live in abject poverty, and are the most vulnerable groups to external disasters, debilitating diseases and untimely death. In addition, the book reveals the theoretical inadequacies that negatively impact ongoing development efforts. Lastly, it identifies an available alternative set of science-based approaches that could facilitate the serious pursuit of equitable progress in South Asia and potentially also in other low and middle income countries.